Answer: The required value of y is 19.
Step-by-step explanation: We are given to find the value of y in the solution to the following system of equations :
![y=12x+7~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)\\\\y=-6x+25~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(ii)](https://tex.z-dn.net/?f=y%3D12x%2B7~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~%28i%29%5C%5C%5C%5Cy%3D-6x%2B25~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~%28ii%29)
Comparing equations (i) and (ii), we get
![12x+7=-6x+25\\\\\Rightarrow 12x+6x=25-7\\\\\Rightarrow 18x=18\\\\\Rightarrow x=\dfrac{18}{18}\\\\\Rightarrow x=1.](https://tex.z-dn.net/?f=12x%2B7%3D-6x%2B25%5C%5C%5C%5C%5CRightarrow%2012x%2B6x%3D25-7%5C%5C%5C%5C%5CRightarrow%2018x%3D18%5C%5C%5C%5C%5CRightarrow%20x%3D%5Cdfrac%7B18%7D%7B18%7D%5C%5C%5C%5C%5CRightarrow%20x%3D1.)
From equation (i), we get
![y=12\times1+7=12+7=19.](https://tex.z-dn.net/?f=y%3D12%5Ctimes1%2B7%3D12%2B7%3D19.)
Thus, the required value of y is 19.
Answer:
7, -1
Step-by-step explanation:
x^2 - 6x + 7 = 0
(x - 7)(x + 1) = 0
==> x = 7, x = -1
Answer:
I also think 62 correct me if I'm wrong
Answer: u spelt answer wrong f ( x f ( x ) = -x^3 + 3x^2 + 4x -5 x = -3
Step-by-step explanation: